CEAP-classes and symptoms in people with varicose veins - Kroeger, K.; Ose, C.; Rudofsky, G.; Roesener, J.; Hirche, H. (Phlebologie, 2005)
Individual symptoms of patients with varicose veins are not considered in the CEAP-classification. Method: We analysed how far people with CEAP class 1 and 2 differ in their symptoms from people without varicose veins in the Duesseldorf/ Essen civil servants study recruiting 9935 employees. All volunteers were asked to fill out a questionnaire and were clinically examined. Primarily the clinical findings were documented adapted to the Basel Study and later modified according to the CEAP classification: 64% class 0 (no visible or palpable clinical signs of venous disease), 27% class 1 (small cutaneous veins and/or reticular veins) and 9 class 2 (varicose veins). Results: Leg swelling and muscle cramps during night were the most frequent symptoms in both classes. Statistically the frequency of symptoms in volunteers classified as CEAP class 1 respectively 2 were different from volunteers showing CEAP class 0 but were not different from each other. Grouping the symptoms restless legs, itching and cramps and calculating odds ratios for none of these showed significant results. Especially in women suffering from CEAP class 2 a significant small odds ratio of 0.5 (95%CI: 0.4–0.6) indicated that women rid of all these three symptoms had less frequently a varicosis disease. Conclusion: It can be assumed that the clinical differentiation into CEAP classes also differentiates groups of people with different symptoms.
Keywords: CEAP classification; varicose veins; swelling; cramps; restless leg